P.033 Experiences with epilepsy treatments: a qualitative content analysis of online patient support group discussions. (2nd June 2017) - Lapalme-Remis, S; Kumbamu, A; Young, C; Aase, L; Jetté, N; Leep Hunderford, A
Abstract : Background: To promote patient-centred care in epilepsy, it is essential to understand the issues most important to patients. Literature on patient perceptions of epilepsy treatments is sparse. One source of data is online patient support groups. Patients turn to social media for support from other patients and often express viewpoints not shared with healthcare providers.Methods: Using a qualitative content analysis approach, we analyzed major online epilepsy patient support groups. We initially selected a month-long discussion text across these forums, and further threads were sampled with maximum variation until theme saturation was reached. For data coding and analysis, we employed a combination of a priori codes and emergent codes, using NVivo 11 for data analysis.Results: In our preliminary analysis, we identified topics and categorized them into themes: 1) differential perceptions and understandings of epilepsy; (2) understanding treatment options; (3) experiences of physiological and psychological treatment side effects; (4) concerns about healthcare providers' knowledge and communication regarding treatments.Conclusions: Preliminary results indicate a variety of patient perceptions and understandings of epilepsy and its treatments. Our findings also suggest that patient educational needs should be addressed by incorporating their understanding and concerns. Shared-decision making tools informed by patient perceptions could help healthcare providers better communicate treatment options with patients.